Clinical Observation of Extensively Hydrolysis Protein Formula With Feeding Intolerance in Preterm Infants - Yin, Liping; Ma, Jingjing; Liu, Heng; Gu, Qianying; Huang, Li; Mu, Qi; An, Ning; Qian, LiJuan; Qiao, Lixing (Frontiers in Pediatrics, 2022)
Objective: To investigate whether feeding extensively hydrolysis protein formula during the NICU hospitalization was more beneficial for preterm infants with gestational age (GA)≤34 weeks when breastfeeding was not possible. Methods: 587 preterm infants were randomly divided into two groups, observation groups fed with extensively hydrolyzed formula (EHF) milk, control groups fed with standard preterm formula (SPF) milk until discharge from the neonatal intensive care unit (NICU). The incidence of complications during hospitalization was recorded in both groups. Then, two groups were uniformly fed with 0-to-6-month infant formula milk and followed up for 6 months after discharge. Results: The final study included 370 premature infants, including 185 babies in the observation group and 185 in the control group. In contrast to the SPF, feeding EHF among preterm infants of GA< 34 weeks during NICU hospitalization significantly reduced the incidence of feeding intolerance (FI) (14.1% vs 30.3%, P<0.01). The incidence of necrotizing enterocolitis (NEC) was significantly reduced in the observation group (2.2% vs 6.5%, P<0.05), but there was no significant difference in the incidence of other related complications. At discharge, there were no difference in total serum protein (46.6g/L vs 46.4g/L), albumin (33.5g/L vs 34.2g/L), and calcium (2.37mmol/L vs 2.35mmol/L), but the serum phosphorus concentrations associated with skeletal mineralization (2.10mol/L vs 2.22mmol/L, P<0.05) was significantly reduced and alkaline phosphatase significantly rose (254 IU/L vs 220 IU/L, P<0.05) in the observation group. No significant difference was found in the growth rate of body weight, head circumference, or body length, either during the NICU hospitalization or during the 6-month follow-up after discharge (P> 0.05). Conclusions: Feeding premature infants of GA≤34 weeks with EHF reduced the incidence of FI but has no advantage in establishing whole intestinal nutrition, shortening parenteral nutrition (PN) time, or hospitalization time. It had little effect on physical growth or development during NICU hospitalization and within 6 months after discharge. However, it may increase the incidence of metabolic bone disease (MBD).